Death and life Valley. Environmental memory of the Pomeranian crime of 1939 in Chojnice - Smykowski, Mikołaj; Kobiałka, Dawid (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2023)
The article concerns the environmental histories of Death Valley, Chojnice, Poland, the execution site from the Second World War. The authors discuss the historical and archaeological evidence related to German mass crimes committed near the town during the war, especially in the environmental context of the killing sites. The main assumption is to show – based on an ethnographic field study – that Death Valley despite its designation, appears in local memory as a lively place. Through the lens of environmental anthropology, it is possible to identify those natural features of mass killing sites that not only have not yet been included in the mainstream of historical and archaeological research but Death and life valley. Environmental memory of the pomeranian crime of 1939 in Chojnice also are essential to the present vernacular recognition of environmental specificity of Death Valley’s post-war landscape.